LANGUAGE LEARNING STRATEGIES USED BY JUNIOR HIGH SCHOOL EFL LEARNERS - Amir, Melvina (LLT Journal: A Journal on Language and Language Teaching, 2018)
Research on language learning strategies has been carried out since the 1990s in Indonesia. These studies have covered the language learning strategies among senior high school and university students. There has been insufficient research that investigates junior high school and primary school students. The main objective of the study was to investigate the language learning strategies of junior high school students in learning English by finding out what learning strategies they employ most frequently according to four language skills. Data were collected using survey questionnaire with 34 eight grade students. They responded to the questionnaire adapted from Language Strategy Use Inventory by Cohen, Oxford, and Chi (2002). The adapted version of Language Strategy Use Questionnaire consists of 40 statements concerning the four major English Language Skills. They are listening, speaking, reading and writing. The responses calculated through statistical analysis in terms of frequency, mean and standard deviation by using Statistical Package for Social Science (SPSS) 20 for Windows. The findings revealed that the eight grades of junior high school students in Bandung were moderate users of reading, writing, listening, and speaking. These students were reported to use reading strategies the most while speaking strategies were used less. The findings of this study indicate that the students had their own learning preferences and strategies in learning English. It is recommended that research on language learning strategies should not stop from investigation and exploration in order to help the learner to be successful English language learner.